Characterising protein and amino acid requirements and metabolism in humans, dogs and cell lines with stable isotope methods - Lewis, Jonathan S (2023)
This thesis assesses the amino acid stable isotope methods for measuring aspects of protein metabolism (amino acid oxidation, muscle protein synthesis and albumin synthesis), in dogs, humans and C2C12s. Minimally invasive methods are increasingly important in assessing protein metabolism particularly in companion animals and for vulnerable humans e.g. critically ill. Therefore, the assessment of the stable isotope methods to measure protein metabolism is important. In the dog model, methionine was used to refine the indicator amino acid oxidation (IAAO) technique to a non invasive ‘free living’ method. The results from this experiment produced a low variability between the 95% confidence interval surround the breakpoint value (0.33-0.36 g/1000kcal of methionine on a 95kcal/kgBW0.75), suggesting a refinement in the IAAO method in dogs. In the human model, muscle and albumin FSR were used to assess the impact of the combined supplementation of whey protein (40g) with and without HMB (3g) in elderly males and females. The results indicated a significant increase in the muscle FSR (0.059 ± 0.015 vs. 0.078 ± 0.01 %/h-1, p=0.0173) of elderly women supplemented with both whey protein and HMB and not in elderly males. The sexual dimorphism in elderly people suggests that the treatment in protecting muscle mass should take gender into account. In the C2C12, the rate of protein synthesis was compared when grown on animal and plant hydrolysates when leucine concentrations were matched. There was no difference between the FSR when provided the different protein sources at a matched leucine concentration. These techniques have assessed the variety and capabilities of amino acid stable isotopes for assessing aspects of protein metabolism generally minimally invasively, however muscle protein synthesis in vivo requires more invasive measures.